Inter-relationship between combining ability effects for oil and yield traits in sunflower (Helianthus annuus) - Binodh, Ashish K; Manivannan, N; Varman, P Vindhya (The Indian Journal of Agricultural Sciences, 2012)
The investigation clearly indicated that the parental lines 234 A, 851 A and the testers CSFI 5014 and CSFI 5414 could be used as potential donors for improving seed and oil yield along with oil content. The hybrids, viz. CSFH 6009 (234 A × CSFI 5418), CSFH 6008 (234 A × CSFI 5014) CSFH 6021 (851 A × CSFI 5434) and CSFH 6025 (851 A × CSFI 5414) were found to be desirable based on sca effects for yield and yield contributing traits. The present investigation on inter- relationship of gca with sca revealed the predominance of non-additive gene action, viz. additive × dominance and dominance × dominance type gene interaction for most of the hybrid combinations which could be exploited for heterosis breeding programme in sunflower.